Lead isotopic analyses of copper ores in the Early Bronze Age central Hexi Corridor, north-west China - Chen, G; Cui, Y; Liu, R; Wang, H; Yang, Y; Pollard, AM; Li, Y (Wiley, 2020)
This paper explores the possible provenance of ores employed for metallurgical production during the Early Bronze Age in the central Hexi Corridor of north‐west China. In total, 78 pieces of copper (Cu) ore samples were collected from five Early Bronze Age sites and one Cu deposit site (the Beishantang Cu deposit) in the Heihe River region of the central corridor. These sites were dated to the late Machang (4100–4000 bp), Xichengyi (4000–3700 bp), Qijia (4000–3600 bp) and Siba (3700–3400 bp) cultures. After comparing with published lead (Pb) isotopic data from other possible Cu deposits in north‐west China, the results show that the Cu ores collected from the Early Bronze Age sites were most likely derived from the adjacent Beishan Cu deposit. More intriguingly, for the first time in Hexi Corridor, a dozen Cu ores were discovered containing highly radiogenic Pb. Though fundamentally different from those in the Central Plains, they illustrate a possible new type of Cu used in Bronze Age western China, and the first‐hand materials are significant for further understanding the provenance of raw metals for metallurgical production in the prehistoric Hexi Corridor.